2017
DOI: 10.1093/cid/cix909
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serotype 4,[5],12:i:- in Swine in the United States Midwest: An Emerging Multidrug-Resistant Clade

Abstract: Salmonella 4,[5],12:i:- currently circulating in swine in the US Midwest are likely to be part of an emerging multidrug-resistant clade first reported in Europe, and can carry plasmid-mediated resistance genes that may be transmitted horizontally to other bacteria, and thus may represent a public health concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
149
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(176 citation statements)
references
References 33 publications
14
149
3
1
Order By: Relevance
“…Both isolates of S. 4,[5],12:i:-utilized in animal studies #2 and #3 belonged to the ST34 sequence type, harbored the ASSuT resistance profile, and are likely part of a recently emerged clade of S. 4,[5],12:i:-that appears to be the predominate clade in swine production in the United States (59). The S. Typhimurium isolates belonged to the ST19 sequence type which has been circulating in the Midwest since 2000 (59); this provides additional evidence that suggests that the S. 4,[5],12:i:isolates selected did not evolve from local S. Typhimurium but instead are more similar to a multi-drug resistant clade first reported in Europe (10). Based on the commonality between previously described circulating strains of S. 4, [5],12:i:-and S. Typhimurium, it is reasonable to suggest that the pathogenicity results presented here are representative of the circulating S. 4, [5],12:i:-and S. Typhimurium isolates within swine production systems in the Midwest United States today.…”
Section: Discussionmentioning
confidence: 99%
“…Both isolates of S. 4,[5],12:i:-utilized in animal studies #2 and #3 belonged to the ST34 sequence type, harbored the ASSuT resistance profile, and are likely part of a recently emerged clade of S. 4,[5],12:i:-that appears to be the predominate clade in swine production in the United States (59). The S. Typhimurium isolates belonged to the ST19 sequence type which has been circulating in the Midwest since 2000 (59); this provides additional evidence that suggests that the S. 4,[5],12:i:isolates selected did not evolve from local S. Typhimurium but instead are more similar to a multi-drug resistant clade first reported in Europe (10). Based on the commonality between previously described circulating strains of S. 4, [5],12:i:-and S. Typhimurium, it is reasonable to suggest that the pathogenicity results presented here are representative of the circulating S. 4, [5],12:i:-and S. Typhimurium isolates within swine production systems in the Midwest United States today.…”
Section: Discussionmentioning
confidence: 99%
“…For example, S. Typhimurium DT 104 was globally disseminated in the 1990s and Esaki et al (2004) reported that 40Á7% of S. Typhimurium isolated from food-producing animals were DT104 in 2001 in Japan. A monophasic variant of S. Typhimurium with antigenic structure S. 4, [5],12:i:-(S. 1,4,[5],12:i:-) was recently recognized as an emerging pathogen in many countries and is considered an important epidemic health risk due to the relatively rapid emergence of clones that often exhibit multidrug resistance (EFSA 2010;Gymoese et al 2017;Elnekave et al 2018;EFSA/ECDC 2019). Although human Salmonella infection has been significantly decreasing in Japan since 2000, approximately 300-600 human isolates are reported by prefectural/municipal public health institutes and health centres each year, and S. Typhimurium and S. 4, [5],12:i:-were the most frequently observed serovars from human since at least 2014 (National Institute of Infectious Diseases Japan 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there is rising concern with an emerging serotype, Salmonella enterica serotype 4,[5],12:i:-in swine. This is a potential monophasic variant of Salmonella Typhimurium, and highly resistant to multiple drugs, including ampicillin, streptomycin, sulfonamides and tetracyclines (Elnekave et al, 2018). The serotype is most commonly linked to pork products, and was responsible for a substantial recall of whole roaster hogs from the state of Washington, but was not been linked to feed (Elnekave et al, 2018).…”
Section: Ta B L E 3 Classification Of Risk Based On the Combination Omentioning
confidence: 99%
“…This is a potential monophasic variant of Salmonella Typhimurium, and highly resistant to multiple drugs, including ampicillin, streptomycin, sulfonamides and tetracyclines (Elnekave et al, 2018). The serotype is most commonly linked to pork products, and was responsible for a substantial recall of whole roaster hogs from the state of Washington, but was not been linked to feed (Elnekave et al, 2018). Recently, S. enterica serotype 4,[5],12:i:-has again been linked to swine; a recall of pig ears intended to be used as pet treats was linked to illness in at least 93 people in 27 states (CDC, 2019).…”
Section: Ta B L E 3 Classification Of Risk Based On the Combination Omentioning
confidence: 99%